(untitled) (The Peerian Journal, 2022)
This article discusses the main issues of adapting future teachers to their professional activities during their internship. Ensuring that students’ theoretical knowledge is integrated with the practical process helps students to understand the many facets of the educational profession, the level of their ability, passion, ability, skill in this profession.